Elastomeric/antibacterial properties in novel random Ricinus communis based-copolyesters. (October 2020) - Totaro, Grazia; Sisti, Laura; Cionci, Nicole Bozzi; Martinez, Gonzalo A.; Di Gioia, Diana; Celli, Annamaria
Abstract: Poly(ricinoleic acid) (PRA), coming from the self-polycondensation of ricinoleic acid (RA), which derives from castor oil, is a very interesting polymer because of its intrinsic antimicrobial activity. However, its mechanical properties are insufficient for whatever application, thus copolymerization is required. In this work, two polyesters based on 1, 3 propanediol (PD), such as poly(propylene terephthalate) (PPT) and poly(propylene isophthalate) (PPI), were chosen to prepare random copolyesters containing ricinoleate units. Different content of RA have been tested, such as 10 and 25 mol% respect to the comonomer (terephthalic or isophthalic dimethylester), to evaluate the lowest composition able to confer antibacterial activity. The materials were tested against Staphylococcus aureus and Escherichia coli, and 25 mol% of RA unit resulted to impart antimicrobial activity. Furthermore, thermal properties (DSC and TGA) as well as the elastomeric response of films were investigated. The copolymer PPI/PRA containing 10 mol% of RA presents very high elongation at break, around 1300%. Therefore, by tuning the RA amount it is possible to obtain outstanding elastomeric or antibacterial materials, suitable for textiles and/or film engineering applications. Highlights: Ricinoleic acid from biomass is suitable to be used in polycondensation reactions. Copolymers properties can be tuned as a function of ricinoleic acid content. Copolymers richest in ricinoleic acid have significant antibacterial activity. The copolymer of PPI containing 10 mol% of ricinoleic acid unit presents very high elongation at break. Copolymers with ricinoleic acid could be suitable for textile fibers and/or film engineering thermoplastic applications.